User experience assessment of a COVID-19 tracking mobile application (AMAN) in Jordan - Ashraf Mousa Saleh; Hayfa Y. Abuaddous; Odai Enaizan; Fahad Ghabban (Institute of Advanced Engineering and Science, 2021)
This study assesses the user experience of a COVID-19 tracking application, as employed as a case study of AMAN mobile application based on user experience. This paper proposed an assessment of user experience (UX) for AMAN application (COVID-19 tracking mobile application in Jordan) by implementing a user experience questionnaire tool. The study aims to get feedback and identify UX based on user interaction and usage with the tracking application. The data are taken from 1208 participants who have experience using the application; an online questionnaire was implemented and distributed through social media groups. The research method that was adopted used the instrument from user experience questionnaire (UEQ) of Arabic and English versions. The results from the UX assessment using UEQ showed that there are four scales which are categorized as excellent; they are Attractiveness (Mean=1.9), Efficiency (Mean=2.4), Dependability (Mean=2.1), Stimulation (Mean=1.8), while the two scales on the benchmark of good are Perspicuity (Mean=2.0) and Novelty (Mean=1.6). From the scores, above < 0.8 show a positive evaluation. All scores are above >0,08 indicating that the evaluation of UX has a positive impression. It can be concluded that the AMAN application is very good–satisfying users to track infected cases of COVID 19.